DIURETIC POTENTIAL OF MUMIJO: EXPERIMENTAL EVALUATION AND MECHANISTIC INSIGHTS - Boltabaeva Dilbarkhon Fayzirakhmanovna (Web of Journals Publishing, 2025)
Mumijo, also known as Shilajit, is a natural substance with a rich history in traditional medicine. Recently, scientific investigations have focused on its potential therapeutic effects, particularly its impact on fluid balance and kidney function. This article examines the diuretic effect of Mumijo, assessing its influence on water intake, urinary output, and the excretion of key electrolytes such as sodium, potassium, and creatinine. Our study presents experimental data showing that Mumijo supplementation increases both water consumption and urine output significantly compared to the control group. Furthermore, it enhances the excretion of sodium and potassium, while having a minimal effect on creatinine levels. The results suggest that Mumijo may have significant diuretic properties, with potential applications in the management of fluid balance disorders.
Keywords: Mumijo, diuretic effect, renal function, fluid balance, natriuresis, Wistar rats, traditional medicine, electrolyte excretion, pharmacological properties.